LEARNING FOR CHILDREN WITH DOWN SYNDROME - Olivia, Francisca; Ferreira Sampaio, Salma; Florêncio, Rutemara (Health and Society, 2024)
This article addresses the learning of children with Down Syndrome (DS). The objective was to understand how the teaching and learning process of children with DS occurs and how their limitations can be overcome and/or alleviated. Bibliographical research, with a qualitative, exploratory approach, allowed us to understand the main characteristics presented by children with DS, as well as those that imply learning disorders and, also, about how these subjects learn and which techniques and methods help in their schooling process. During this study, it was possible to observe the importance of mediation in the educational process of children with DS, as well as the means used to stimulate the understanding of educational content and guarantee the same learning opportunities.